Staley: the fight for a new American labor movement - Ashby, Steven K.; Hawking, C.J. (Urbana, 2009)
"This on-the-ground labor history chronicles the bitterly contested labor conflict in the mid 1990s at the A. E. Staley corn processing plant in Decatur, Illinois, where workers waged one of the most hard-fought struggles in recent labor history. When the company launched a full-scale assault on its workers, Allied Industrial Workers Local 837 responded by educating and mobilizing its members, organizing strong support from the religious and African American communities, building a nationwide solidarity movement, and engaging in nonviolent civil disobedience at the plant gates. Through scores of interviews and videotapes of every union meeting, the authors bring the workers' voices to the fore and reveal their innovative tactics that inform and strengthen today's labor movement."